Bru-ha-ha-ha-ha-ha... bru-hi-hi-hi-hi-hi... - Remigio, Ma Corazon; Ilagan, Roland Mechael (Quezon City Adarna House, 1995)
A story of a little girl and an old lady rumored to be a witch
Rekomendado sa mga batang edad 10 pataas.
Text in Filipino and English.
PBBY Salanga Writer's Prize.
PBBY Illustrator's Prize.